Factors Affecting the Continuance Intention to Use Food Delivery Apps of The Millennials in Ho Chi Minh City - Le Giang Nam; Thuan An, Nguyen Thi (Technium Social Sciences Journal, 2021)
Food delivery apps (FDAs) have experienced a meteoric rise in recent years, especially amidst the COVID-19 pandemic and the resulting governmental orders for social distancing. Though FDAs have been attracting significant interest in Vietnam and other Southeast Asian countries, the related issues of these apps have not been fully studied by academics and researchers. Additionally, most previous studies of mobile apps in general and FDAs in particular have simply addressed aspects related to intention to use and initial adoption of Vietnamese people. Hence, this research aims to go further by examining customers’ satisfaction and their continuance intention to use (CI). Rather than being conducted on general customers as most previous studies, this study focuses on Millennials, a particular age group with distinctive characteristics, shopping habits and motivations (European Union, 2020). As this generational cohort proves to be the drivers for food delivery services, their crystal-clear insights when deciding to use FDAs continuously are undoubtedly valuable. This research proposed an integrated model incorporating UTAUT2, ECM, TTF and the variable of “Price-saving Orientation”. Based on the Structural Equation Modeling (SEM), the findings supported all hypotheses, with Performance Expectancy (PE) validated to be the most influential factor shaping continuance intention to use FDA amongst the Millennials in Ho Chi Minh (HCM) city. Theoretical contributions and managerial implications derived from these findings presented practical guidance for academics and key participants within the FDA-related landscape.